FITOREMEDIASI AIR LIMBAH TEMPE MENGGUNAKAN TUMBUHAN KAYU APU (PISTIA STRATIOTES) - Rosa Masita As'ari; Achmad Syafiuddin; Agus Aan Andriansyah; Budhi Setianto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
ABSTRACTDevelopment industrialization for Fulfill needs Public impact on pollution environment because discarded waste produce substance dangerous for body. Phytoremediation is a technological process that can use plants to restore soil or areas contaminated with waste. The purpose of this study was to analyze the effect of Apu. wood in the phytoremediation test of tempe wastewater with parameters TSS, COD, BOD and pH. This type of research is a quantitative research. This research was conducted to determine the effect of Kayu Apu ( Pistia Stratiotes ) plants in phytoremediation tests on tempe waste. Research using true experimental methods, Apu wood ( Pistia Stratiotes ) as many as 15 plants will be directly contacted with a tub containing wastewater, then as a comparison, 6 plants are placed in another tub that will be in direct contact with wastewater. The duration of the water treatment was carried out for 3 levels with a contact time of day 0, 3 days (72 hours) and 5 days (120 hours). From the results of the study, the Apu Wood (Pistia Stratiotes) decreased in the TSS parameter from 446.77 mg/L down to 226.64 mg/L , COD from 1.765.74 mg/L decreased to 953.77 mg/L , BOD from 978.84 mg/L down to 458.66 mg/L and changes in pH parameters. Researcher next expected no To do research on season rain because plant need light for photosynthesis, researcher expected use combination another method with phytoremediation, dilution with water or add substance other chemicals for plants can last long in treatment. Keywords: Phytoremediation, Kayu Apu, BOD, COD